Boron nitride particles, resin composition, and method for producing resin composition

By developing new boron nitride particles with shapes with gradually increasing diameters and combining them with resins into resin compositions, the problem that existing boron nitride particles are not suitable for use in efficient heat dissipation materials is solved, and more efficient thermal conductivity and Heat dissipation effect.

CN115697898BActive Publication Date: 2025-02-25DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180038631.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-20
Filing Date
2021-08-19
Publication Date
2025-02-25
Estimated Expiration
2041-08-19

AI Technical Summary

Technical Problem

The shape of the existing boron nitride particles is not suitable for efficient heat dissipation materials, resulting in poor thermal conductivity.

Method used

A new type of boron nitride particle has a shape with a diameter gradually increasing from one end to the other end, and is combined with a resin to form a resin composition to optimize the shape and distribution of the particles by specific manufacturing methods and processes.

Benefits of technology

By optimizing the shape of boron nitride particles, it is easier to stand in the thickness direction of the heat dissipation material, reduce heat conductivity and heat dissipation performance of the heat dissipation material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115697898B_ABST
    Figure CN115697898B_ABST
Patent Text Reader

Abstract

Boron nitride particles having a shape in which the diameter gradually increases from one end to the other end. Boron nitride particles having a plurality of parts having a shape in which the diameter gradually increases from one end to the other end, the plurality of parts being bonded to each other at the other end side.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to boron nitride particles, a resin composition, and a method for producing the resin composition. Background Art

[0002] Boron nitride has lubricity, high thermal conductivity, and insulation properties, and is used in a variety of applications, including solid lubricants, mold release materials, raw materials for cosmetics, heat dissipation materials, and sintered bodies with heat resistance and insulation properties.

[0003] For example, Patent Document 1 discloses a hexagonal boron nitride powder that can impart high thermal conductivity and high insulation resistance to a resin composition filled with a resin, wherein the hexagonal boron nitride powder comprises aggregated particles formed of primary particles of hexagonal boron nitride and has a BET specific surface area of ​​0.7 to 1.3 m 2 / g, and the oil absorption measured based on JIS K 5101-13-1 is 80 g / 100 g or less.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-160134 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The main purpose of the present invention is to provide novel boron nitride particles.

[0009] Means for solving problems

[0010] One aspect of the present invention is a boron nitride particle having a shape in which the diameter gradually increases from one end to the other end.

[0011] The length from the one end to the other end may be 80 μm or more.

[0012] Another aspect of the present invention is a boron nitride particle including a plurality of portions having a shape in which the diameter gradually increases from one end toward the other end, wherein the plurality of portions are bonded to each other at the other end side.

[0013] A length of the plurality of portions in a direction from the one end to the other end may be 80 μm or more.

[0014] Another aspect of the present invention is a resin composition comprising the above-mentioned boron nitride particles and a resin.

[0015] Another aspect of the present invention is a method for producing a resin composition, comprising the steps of: preparing the boron nitride particles; and mixing the boron nitride particles with a resin. The method for producing a resin composition may further comprise a step of pulverizing the boron nitride particles.

[0016] Effects of the Invention

[0017] According to one aspect of the present invention, novel boron nitride particles can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] [ Figure 1 ] is a graph showing the X-ray diffraction measurement results of the boron nitride particles of Example 1.

[0019] [ Figure 2 ] is a SEM image of the boron nitride particles of Example 1.

[0020] [ Figure 3 ] is a SEM image of the boron nitride particles of Example 2.

[0021] [ Figure 4 ] is a SEM image of the boron nitride particles of Example 3. DETAILED DESCRIPTION

[0022] Embodiments of the present invention will be described in detail below. One embodiment of the present invention is a boron nitride particle (the boron nitride particle is referred to as a boron nitride particle A) having a shape in which the diameter gradually increases from one end to the other end.

[0023] In this specification, the direction from one end to the other end of the boron nitride particle A is defined as the axial direction, and the direction perpendicular to the axial direction is defined as the radial direction. In addition, in this specification, the diameter of the boron nitride particle A refers to the size of the boron nitride particle in the radial direction.

[0024] In the past, boron nitride particles were flaky, spherical or irregular in shape. In contrast, the diameter of the boron nitride particles A involved in one embodiment gradually increases from one end of the boron nitride particles to the other end. Therefore, it is believed that since the center of gravity of the boron nitride particles A is located at the other end side in the axial direction, when the boron nitride particles A are used for heat dissipation materials (heat sinks), one end side (the side with a relatively small diameter) is on top and the other end side (the side with a relatively large diameter) is on the bottom, so that it is easy to stand in the thickness direction of the heat dissipation material. Therefore, the boron nitride particles A can be preferably used for heat dissipation materials. It should be noted that although the use of the boron nitride particles A as heat dissipation materials is illustrated, the boron nitride particles A are not limited to heat dissipation materials and can be used for various purposes.

[0025] The fact that the boron nitride particle A has the above-mentioned shape can be confirmed by the following method: in the observation image when the boron nitride particle A is observed by SEM, the diameters of the boron nitride particle A at 10 locations equally spaced in the axial direction of the boron nitride particle A are set to A1, A2, ..., A1 in order from one end of the boron nitride particle A to the other end. 10 (The diameter of one end of the boron nitride particle A is A1 and the diameter of the other end is A 10 ), A1, A2, ···, A 10 The diameter A of the boron nitride particle A is n (n is an integer of 2 to 10) preferably in A2 to A 10 All 9 places are larger than diameter A n-1 Big, but A n As long as 8 out of 9 are better than A n-1 The diameter of the boron nitride particle A can also be measured by importing the SEM image into image analysis software (for example, "Mac-view" manufactured by MOUNTECH Co., Ltd.).

[0026] The diameter A of the boron nitride particle A 10 The larger the diameter A1 of the boron nitride particle A is, the more the center of gravity of the boron nitride particle A in the axial direction is located on the other end side. Therefore, it is believed that when the boron nitride particle A is mixed with a resin to be used as a heat dissipation material, the boron nitride particle A is more likely to stand in the thickness direction of the heat dissipation material, so the heat dissipation material has excellent thermal conductivity. 10 The diameter A1 of the boron nitride particle A may be 1.2 times or more, 1.4 times or more, 1.6 times or more, 1.8 times or more, or 2 times or more, and may be 10 times or less, 8 times or less, or 6 times or less.

[0027] The maximum length of the boron nitride particle A in the axial direction can be 80 μm or more, 100 μm or more, 125 μm or more, 150 μm or more, 175 μm or more, 200 μm or more, 225 μm or more, 250 μm or more, 300 μm or more, or 350 μm or more, and can be 500 μm or less. The maximum length of the boron nitride particle A can also be measured by importing the SEM image into image analysis software (e.g., "Mac-view" manufactured by MOUNTECH Co., Ltd.).

[0028] By making the axial length of the boron nitride particles A larger, for example, when the boron nitride particles A stand in the thickness direction of the heat dissipation material as described above, the number of boron nitride particles arranged in the thickness direction of the heat dissipation material decreases, and the heat conduction loss between the boron nitride particles decreases. Therefore, it is believed that the heat dissipation material has excellent thermal conductivity.

[0029] The maximum value of the diameter of the boron nitride particles A may be 50 μm or more, 80 μm or more, 100 μm or more, 125 μm or more, 150 μm or more, 175 μm or more, 200 μm or more, 225 μm or more, 250 μm or more, 300 μm or more, or 350 μm or more, and may be 500 μm or less.

[0030] The minimum diameter of the boron nitride particles A may be 1 μm or more, 2 μm or more, 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more, and may be 100 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, or 40 μm or less.

[0031] The average diameter of the boron nitride particles A (the diameter A1 to A 10 The average value of the above-mentioned material) can be greater than 10 μm, greater than 15 μm, greater than 20 μm, greater than 25 μm, greater than 30 μm, greater than 40 μm, or greater than 50 μm, and can be less than 200 μm, less than 150 μm, less than 100 μm, less than 80 μm, less than 70 μm, or less than 60 μm.

[0032] The aspect ratio of the boron nitride particle A may be 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 2.0 or more, 3.0 or more, 5.0 or more, or 7.0 or more, and may be 12.0 or less, 10.0 or less, 9.5 or less, 9.0 or less, or 8.0 or less. The aspect ratio of the boron nitride particle A is defined as the ratio of the maximum length (L1) of the boron nitride particle A in the axial direction to the diameter A1 to A1 of the boron nitride particle A. 10 The ratio (L1 / L2) of the average value (L2).

[0033] The larger the aspect ratio of the boron nitride particles A is, the more elongated the shape of the boron nitride particles A is. Therefore, it is believed that, for example, when the boron nitride particles A are mixed with a resin to be used as a heat dissipation material, the boron nitride particles A become easy to overlap with other boron nitride particles. In addition, when the boron nitride particles A overlap with other boron nitride particles, the elongated boron nitride particles A overlap in an inclined manner. Therefore, it is believed that the number of boron nitride particles arranged in the thickness direction of the heat dissipation material decreases, and the heat conduction loss between the boron nitride particles decreases, so the heat dissipation material has excellent thermal conductivity.

[0034] The boron nitride particles A may be solid or hollow. When the boron nitride particles A are hollow, the boron nitride particles A may have an outer shell formed by boron nitride and a hollow portion surrounded by the outer shell. The hollow portion may extend along the axial direction of the boron nitride particles A, or may be a shape that is roughly similar to the appearance of the boron nitride particles A. In this case, the boron nitride particles A may also be tubular boron nitride particles whose diameter gradually increases from one end to the other end.

[0035] One or both of one end and the other end of the boron nitride particle A may be an open end. The open end may be connected to the hollow portion. The boron nitride particle A is hollow, and at least one of one end and the other end of the boron nitride particle A is an open end. Thus, for example, when the boron nitride particle A is mixed with a resin and used as a heat dissipation material, by filling the hollow portion with a resin lighter than the boron nitride particle A, it is possible to simultaneously expect to have thermal conductivity and light weight of the heat dissipation material.

[0036] In another embodiment, the boron nitride particles may be boron nitride particles having a plurality of portions having a shape in which the diameter gradually increases from one end to the other end, and the plurality of portions are bonded to each other at the other end side (these boron nitride particles are referred to as boron nitride particles B).

[0037] In the boron nitride particle B, the direction from one end to the other end of each part is defined as the axial direction, and the direction perpendicular to the axial direction is defined as the radial direction. The confirmation method for each part of the boron nitride particle B having the above-mentioned shape may be the same method as the confirmation method for the shape of the above-mentioned boron nitride particle A. The maximum length of each part of the boron nitride particle B in the axial direction may be the same as the range described as the maximum length of the axial direction of the above-mentioned boron nitride particle A.

[0038] In the past, boron nitride particles were scaly, spherical or irregular in shape. In contrast, the boron nitride particles B according to one embodiment have a plurality of parts with a shape whose diameter gradually increases from one end to the other end, and the plurality of parts are combined with each other at the other end side. Therefore, it is believed that since the center of gravity of the boron nitride particles B is located at the other end side (the side where the plurality of parts are combined with each other), when the boron nitride particles B are used for heat dissipation materials (heat sinks), the other end side is at the bottom, so that it is easy to stand in the thickness direction of the heat dissipation material. Therefore, the boron nitride particles B can also be preferably used for heat dissipation materials. It should be noted that the boron nitride particles B are not limited to heat dissipation materials and can be used for various purposes.

[0039] Boron nitride particle B can be solid or hollow. When the boron nitride particle B is hollow, the boron nitride particle B can have an outer shell formed by boron nitride and a hollow portion surrounded by the outer shell. The hollow portion can extend axially in one of the multiple parts of the boron nitride particle B, or it can extend axially in more than two of the multiple parts. The hollow portion can also be a shape that is roughly similar to the appearance shape of each part of the boron nitride particle B. When the hollow portion extends axially in multiple parts of the boron nitride particle B, the boron nitride particle B can also be a boron nitride particle having multiple parts with a tubular shape whose diameter gradually increases from one end to the other end, and the multiple parts are combined with each other at the other end side.

[0040] One or both of the one end and the other end of each of the multiple parts of the boron nitride particle B can be an open end. The open end can be connected to the above-mentioned hollow portion. Since the boron nitride particle B is hollow and at least one of the one end and the other end of the boron nitride particle B is an open end, when the boron nitride particle B is mixed with a resin and used as a heat dissipation material, for example, by filling the hollow portion with a resin lighter than the boron nitride particle B, it is possible to simultaneously expect to have thermal conductivity and light weight of the heat dissipation material.

[0041] The boron nitride particles (boron nitride particles A and boron nitride particles B) may be substantially composed of only boron nitride. That the boron nitride particles are substantially composed of only boron nitride can be confirmed by detecting only a peak derived from boron nitride in X-ray diffraction measurement.

[0042] Next, the method for producing the above-mentioned boron nitride particles (boron nitride particles A and boron nitride particles B) is described below. The above-mentioned boron nitride particles can be produced by, for example, a method for producing boron nitride particles having the following steps: a step of disposing a mixture containing boron carbide, boron nitride and boric acid, and a substrate formed of a carbon material in a container formed of a carbon material (disposition step); a step of generating boron nitride particles on the substrate by heating and pressurizing the container in a nitrogen atmosphere (generation step). Another embodiment of the present invention is a method for producing such boron nitride particles.

[0043] The container formed by the carbon material is a container capable of accommodating the above-mentioned mixture and the substrate. The container may be, for example, a carbon crucible. The container is preferably a container that can improve airtightness by covering the opening with a lid. In the configuration step, for example, the mixture may be configured at the bottom of the container, and the substrate may be configured in a manner that is fixed to the side wall surface in the container and the inner side of the lid. The substrate formed by the carbon material may be, for example, in the form of a sheet, a plate or a rod. The substrate formed by the carbon material may be, for example, a carbon sheet (graphite sheet), a carbon plate or a carbon rod.

[0044] By adjusting the distance between the mixture and the substrate surface, the diameter of one end of the boron nitride particle can be adjusted. When the distance between the mixture and the substrate surface is far (e.g., more than 2.0 cm), the diameter of one end of the boron nitride particle tends to be less than half of the diameter of the other end.

[0045] The boron carbide in the mixture can be, for example, in a powdered state (boron carbide powder). The boron nitride in the mixture can be, for example, in a powdered state (boron nitride powder). The boric acid in the mixture can be, for example, in a powdered state (boric acid powder). The mixture can be obtained, for example, by mixing boron carbide powder, boron nitride powder and boric acid powder using a known method.

[0046] Boron carbide powder can be manufactured by a known manufacturing method. As a manufacturing method of boron carbide powder, for example, the following method can be cited: after mixing boric acid and acetylene black, heating at 1800 to 2400° C. for 1 to 10 hours in an inert gas (e.g., nitrogen gas) atmosphere to obtain blocky boron carbide particles. The blocky boron carbide particles obtained by this method are appropriately crushed, sieved, cleaned, impurity removed, dried, etc. to obtain boron carbide powder.

[0047] By adjusting the pulverization time of the massive carbon-boron particles, the average particle size of the boron carbide powder can be adjusted. The average particle size of the boron carbide powder can be 5 μm or more, 7 μm or more, or 10 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, or 70 μm or less. The average particle size of the boron carbide powder can be measured by laser diffraction scattering method.

[0048] Boron nitride powder can be produced by a known production method. As a production method of boron nitride powder, boron nitride powder can be obtained by, for example, mixing boric acid or boron oxide, melamine, and water, removing water from the mixture by filtering, centrifugal separation, drying, etc., and calcining in a non-oxidizing gas atmosphere.

[0049] The average particle size of the boron nitride powder may be 5 μm or more, 7 μm or more, or 10 μm or more, or 100 μm or less, 90 μm or less, 80 μm or less, or 70 μm or less. The average particle size of the boron nitride powder can be measured by laser diffraction scattering.

[0050] The mixing ratio of boron carbide, boron nitride and boric acid can be appropriately selected. Considering from the viewpoint of suppressing the distance change between the mixture and the substrate surface caused by the expansion of boron carbide, relative to 100 mass parts of boron carbide, the content of the boron nitride in the mixture is preferably more than 50 mass parts, more preferably more than 70 mass parts, more preferably more than 80 mass parts, and can be less than 150 mass parts, less than 120 mass parts or less than 100 mass parts. Considering from the viewpoint that boron nitride particles are easy to become larger, relative to 100 mass parts of boron carbide, the content of the boric acid in the mixture is preferably more than 2 mass parts, more preferably more than 5 mass parts, more preferably more than 8 mass parts, and can be less than 100 mass parts, less than 90 mass parts or less than 80 mass parts. Taking the gross mass of the mixture as a benchmark, when the content of the boric acid in the mixture is more than 10 mass %, it is easy to generate boron nitride particles B.

[0051] The mixture containing boron carbide, boron nitride and boric acid may also contain other components. As other components, silicon carbide, carbon, iron oxide, etc. can be cited. By including silicon carbide in the mixture containing boron carbide, boron nitride and boric acid, it is easy to obtain boron nitride particles without open ends.

[0052] The container is provided with a nitrogen atmosphere containing, for example, 95% by volume or more of nitrogen gas. The content of nitrogen gas in the nitrogen atmosphere is preferably 95% by volume or more, more preferably 99.9% by volume or more, and can be substantially 100% by volume. In addition to nitrogen gas, the nitrogen atmosphere may also contain ammonia gas or the like.

[0053] From the viewpoint that the boron nitride particles tend to grow larger, the heating temperature is preferably 1450° C. or higher, more preferably 1600° C. or higher, and further preferably 1800° C. or higher. The heating temperature may be 2400° C. or lower, 2300° C. or lower, or 2200° C. or lower.

[0054] From the viewpoint that the boron nitride particles are likely to grow larger, the pressure during pressurization is preferably 0.3 MPa or more, and more preferably 0.6 MPa or more. The pressure during pressurization may be 1.0 MPa or less, or 0.9 MPa or less.

[0055] From the viewpoint that the boron nitride particles are likely to grow larger, the heating and pressurizing time is preferably 3 hours or longer, more preferably 5 hours or longer. The heating and pressurizing time may be 40 hours or shorter, or 30 hours or shorter.

[0056] According to the manufacturing method, the above-mentioned boron nitride particles can be generated on a substrate formed of a carbon material. Therefore, by recovering the boron nitride particles on the substrate, boron nitride particles can be obtained. In the case where the particles generated on the substrate are boron nitride particles, it can be confirmed by recovering a part of the particles from the substrate, performing X-ray diffraction measurement on the recovered particles, and detecting peaks from boron nitride.

[0057] The boron nitride particles obtained by the above method may be subjected to a step of classifying so as to obtain only boron nitride particles having a maximum length within a specific range (classification step).

[0058] The boron nitride particles obtained by the above method can be mixed with a resin to be used as a resin composition. That is, another embodiment of the present invention is a resin composition containing the above-mentioned boron nitride particles and a resin.

[0059] Examples of the resin include epoxy resins, silicone resins, silicone rubbers, acrylic resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyimides, polyamide-imides, polyetherimides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyesters, polysulfones, liquid crystal polymers, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber·styrene) resins, AES (acrylonitrile·ethylene·propylene·diene rubber-styrene) resins, and the like.

[0060] When the resin composition is used as a heat dissipation material, from the viewpoint of improving the thermal conductivity of the heat dissipation material and facilitating obtaining excellent heat dissipation performance, the content of the boron nitride particles may be 15% by volume or more, 20% by volume or more, 30% by volume or more, 40% by volume or more, 50% by volume or more, or 60% by volume or more based on the total volume of the resin composition. From the viewpoint of being able to suppress the generation of voids when the resin composition is molded into a sheet-like heat dissipation material and suppressing the decrease in the insulation and mechanical strength of the sheet-like heat dissipation material, the content of the boron nitride particles may be 85% by volume or less, 80% by volume or less, 70% by volume or less, 60% by volume or less, 50% by volume or less, or 40% by volume or less based on the total volume of the resin composition.

[0061] The content of the resin can be appropriately adjusted according to the application of the resin composition, required characteristics, etc. Based on the total volume of the resin composition, the content of the resin can be, for example, 15% by volume or more, 20% by volume or more, 30% by volume or more, 40% by volume or more, 50% by volume or more, or 60% by volume or more, and can be 85% by volume or less, 70% by volume or less, 60% by volume or less, 50% by volume or less, or 40% by volume or less.

[0062] The resin composition may further contain a curing agent for curing the resin. The curing agent may be appropriately selected according to the type of the resin. For example, as a curing agent used together with the epoxy resin, phenolic Novolac compounds, acid anhydrides, amino compounds, imidazole compounds, etc. may be cited. Relative to 100 parts by mass of the resin, the content of the curing agent may be, for example, 0.5 parts by mass or more, or 1.0 parts by mass or more, or 15 parts by mass or less, or 10 parts by mass or less.

[0063] The resin composition may further contain other components, such as a curing accelerator (curing catalyst), a coupling agent, a wetting and dispersing agent, and a surface conditioner.

[0064] Examples of the curing accelerator (curing catalyst) include phosphorus-based curing accelerators such as tetraphenylphosphine tetraphenylborate and triphenylphosphate, imidazole-based curing accelerators such as 2-phenyl-4,5-dihydroxymethylimidazole, and amine-based curing accelerators such as boron trifluoride monoethylamine.

[0065] Examples of the coupling agent include silane coupling agents, titanate coupling agents, and aluminate coupling agents, etc. Examples of the chemical bonding groups contained in these coupling agents include vinyl groups, epoxy groups, amino groups, methacryloyl groups, and mercapto groups.

[0066] Examples of the wetting and dispersing agent include phosphate ester salts, carboxylic acid esters, polyesters, acrylic acid copolymers, and block copolymers.

[0067] Examples of the surface conditioner include acrylic surface conditioners, silicone surface conditioners, vinyl surface conditioners, and fluorine surface conditioners.

[0068] The resin composition can be manufactured, for example, by a method for manufacturing a resin composition having the following steps: a step of preparing the boron nitride particles involved in one embodiment (preparation step); a step of mixing the boron nitride particles with a resin (mixing step). Another embodiment of the present invention is a method for manufacturing such a resin composition. In the mixing step, in addition to the boron nitride particles and the resin, the above-mentioned curing agent and other components may also be mixed.

[0069] The method for producing a resin composition according to one embodiment may further include a step of crushing the boron nitride particles (crushing step). The crushing step may be performed between the preparation step and the mixing step, or may be performed simultaneously with the mixing step (the boron nitride particles may also be crushed while mixing the boron nitride particles with the resin).

[0070] The resin composition can be used as a heat dissipation material, for example. The heat dissipation material can be manufactured, for example, by curing the resin composition. The method for curing the resin composition can be appropriately selected according to the type of resin (and curing agent used as needed) contained in the resin composition. For example, when the resin is an epoxy resin and the curing agent is used in combination, the resin can be cured by heating.

[0071] Example

[0072] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.

[0073] (Example 1)

[0074] The blocky boron carbide particles were crushed by a pulverizer to obtain boron carbide powder with an average particle size of 10 μm. 50 parts by mass of the obtained boron carbide powder, 45 parts by mass of boron nitride powder (manufactured by Denka Co., Ltd., GP grade), and 9 parts by mass of boric acid were mixed, and the obtained mixture was filled in a carbon crucible, and the opening of the carbon crucible was covered with a carbon sheet (manufactured by NeoGraf), and the carbon sheet was fixed by clamping the carbon sheet with the lid of the carbon crucible and the carbon crucible. The distance between the mixture and the carbon sheet was 2.0 cm. The carbon crucible with the lid was heated in a resistance heating furnace at 2000°C and 0.85 MPa for 10 hours under the conditions of nitrogen gas atmosphere, thereby generating particles on the carbon sheet.

[0075] A portion of the particles generated on the carbon sheet was recovered and subjected to X-ray diffraction measurement using an X-ray diffractometer (manufactured by Rigaku Corporation, "ULTIMA-IV"). The X-ray diffraction measurement results and the X-ray diffraction measurement results of boron nitride powder (GP grade) manufactured by Denka Co., Ltd. as a comparative object are shown in Figure 1 .Depend on Figure 1 It can be seen that only the peak derived from boron nitride was detected, confirming that boron nitride particles were generated. The SEM image of the obtained boron nitride particles is shown in FIG. Figure 2 One of the obtained boron nitride particles ( Figure 2 The boron nitride particles (indicated by arrows in the figure) have a shape in which the diameter gradually increases from one end to the other end. The maximum length of the boron nitride particles in the axial direction is 184 μm, and the maximum value of the diameter is 108 μm. The diameters of the boron nitride particles at 10 locations equally spaced in the axial direction of the boron nitride particles are set as A1, A2, ..., A1 from one end to the other end of the boron nitride particles. 10 (The diameter of one end of the boron nitride particle is A1 and the diameter of the other end is A 10 ), A1 is 33μm, A 10 108μm, A1~A 10 The average value is 63μm.

[0076] (Example 2)

[0077] The boron nitride powder was changed to SGP grade boron nitride powder manufactured by Denka Co., Ltd. to obtain a mixture, and the distance between the obtained mixture and the carbon sheet was changed to 1.5 cm. Particles were generated on the carbon sheet in the same manner as in Example 1. A portion of the particles generated on the carbon sheet was recovered and subjected to X-ray diffraction measurement. As a result, only peaks derived from boron nitride were detected, thereby confirming that boron nitride particles were generated. The SEM image of the obtained boron nitride particles is shown in FIG. Figure 3 One of the obtained boron nitride particles ( Figure 3The boron nitride particles (indicated by arrows in the figure) have a shape in which the diameter gradually increases from one end to the other end. The maximum length of the boron nitride particles in the axial direction is 153 μm, and the maximum value of the diameter is 106 μm. The diameters of the boron nitride particles at 10 locations equally spaced in the axial direction of the boron nitride particles are set as A1, A2, ..., A1 from one end to the other end of the boron nitride particles. 10 (The diameter of one end of the boron nitride particle is A1 and the diameter of the other end is A 10 ), A1 is 51μm, A 10 106μm, A1~A 10 The average value is 80μm.

[0078] (Example 3)

[0079] Particles were generated on the carbon sheet in the same manner as in Example 1 except that the amount of boric acid was changed to 12 parts by mass to obtain a mixture. A portion of the particles generated on the carbon sheet was recovered and subjected to X-ray diffraction measurement. As a result, only a peak derived from boron nitride was detected, confirming that boron nitride particles were generated. The SEM image of the obtained boron nitride particles is shown in FIG. Figure 4 One of the obtained boron nitride particles ( Figure 4 The boron nitride particles (indicated by arrows in FIG. 1 ) have a plurality of parts having a shape in which the diameter gradually increases from one end to the other end, and the plurality of parts are connected to each other on the other end side.

Claims

1. Boron nitride particles having a shape in which the diameter gradually increases from one end to the other end, the length from the one end to the other end is 80 μm or more, the average value of the diameter is 10 μm or more, and the minimum value of the diameter is 1 μm or more.

2. Boron nitride particles having a plurality of portions having a shape in which the diameter gradually increases from one end to the other end, The plurality of parts are joined to each other at the other end side, The length of the plurality of parts in the direction from the one end to the other end is 80 μm or more, The minimum value of the diameter is 1 μm or more, The average value of the diameter is 10 μm or more.

3. A resin composition comprising: a resin and the boron nitride particles according to claim 1 or 2.

4. A method for producing a resin composition, comprising the following steps: A step of preparing the boron nitride particles according to claim 1 or 2; and A step of mixing the boron nitride particles with a resin. 5 . The method for producing a resin composition according to claim 4 , further comprising the step of pulverizing the boron nitride particles.

Citation Information

Patent Citations

  • Hexagonal boron nitride powder and method for producing the same

    JP2016160134A

  • Heat-resistant resin composite composition and method for producing the same

    JP2008007699A

  • Boron nitride nanofiber and method of manufacturing the same

    JP2009155176A